Social and Environmental Factors as Determinants of Self-Adjustment of Persons with Visual Impairment in Oyo State, Nigeria - Komolafe, Adebayo Francis (Advances in Social Sciences Research Journal, 2016)
Persons with visual impairment often receive inappropriate behaviour from their environment as well as encountering many unpleasant challenges in their effort to cope with vicissitudes of life. Most study on persons with visual impairment tend to focus on the use of assistive visual devices and their academic achievement with little or no studies devoted to factors that can help them to achieve proper self-adjustment within society. This current study therefore examined the social and environmental factors as determinants of self-adjustment of persons with visual impairment in Oyo State of Nigeria. Descriptive survey research design was adopted while purposive sampling technique was used to select one hundred participants for the study. Findings revealed that social and environmental factors were positively correlated with self-adjustment of persons with visual impairment. The joint contribution of social and environmental factors to self-adjustment was significant, F =436.424, P<0.05, accounting for about 89.8% of the variance. The relative contribution of the independent variables to self- adjustment of persons with visual impairment ranked environmental factors (β=0.883,t=27.404, p<0.05) more than the Social factors (β=0.426, t=13.222, p<0.05) in terms of beta. Social and environmental factors are important determinants of self-adjustment of persons with visual impairment. Therefore, it is recommended that family, school and community should accept persons with visual impairment through caring and supportive attitudes, and learn to accommodate them.